Research on traction drive with permanent magnet synchronous motor - Šimánek, Jiří; Černý, Ondřej; Doleček, Radovan (Univerzita Pardubice, 2007)
The paper deals with the description of our research in the field of the traction drive control. The aim of the research is the robust control algorithm for traction drive with permanent magnet synchronous motor (PMSM). The first chapter of the paper deals with the description of a workplace where the research is performed. The workplace contains a testing stand with PMSM, loading asynchronous motor, frequency converter and auxiliary systems. The testing stand contains the low speed PMSM, tram wheel and rotary rail. The wheel is powered by the PMSM directly without any gearings. The PMSM with nominal power of 58 kW was made by VÚES Brno (Research Institute of Electric Machines Brno) like prototype tram traction motor. Due this stand our experiments are applied to the drive with parameters similar to real traction drive of trams. Next chapter is focused on theory of PMSM control. The control is oriented on current space vector position and magnitude. The orthogonality of current space vector and rotor flux vector is the aim of the control. The description of two designed control algorithms is in this chapter, too. The first algorithm is called phase current control which is based on the sinusoidal commutation algorithm of DC brushless motor. Due the several improvements this algorithm has better behavior at higher motor speed than original algorithm. The second algorithm is field oriented control. Both of the algorithms were simulated and the first algorithm was applied to the real drive. The chapter 4 brings results of the simulation. The MATLAB Simulink software has been used for the simulations. The comparison of behavior of both algorithms is mentioned at the end of this chapter. The last chapter brings comparison of simulation results and results from experiments on testing stand. Only the phase current control algorithm was applied to the stand until now, therefore the chapter does not bring any comparison of results of field oriented control with real measurement yet.
Regulační struktury pro trakční pohon se synchronním motorem s permanentními magnety
Keywords: robustní regulační struktura; trakční pohony; synchronní motory; permanentní magnety; regulace fázových proudů